Facilitation of the Dynamics of Social Interaction Skills Development in Preschool Children with Autism Spectrum Disorder - Vasina, Veronika V (International Journal of Social Sciences Perspectives, 2022)
The increase in the number of children with autism spectrum disorders has exacerbated the problem of improving (facilitating) social interaction skills in preschoolers. This category of children is characterized by a combination of qualitative disorders, where one of the main manifestations is difficulties in verbal and social behavior. The aim is to study the dynamics of the development of social interaction skills in preschoolers with autism spectrum disorders, depending on gender and age, to identify points of facilitation, to give recommendations. On the basis of ontological and behavioral approaches, theoretical methods of analysis of philosophical, psychological and pedagogical literature are used, among the empirical methods are the Sundberg method VB-MAPP (2008), observations, qualitative analysis, Student’s T-criterion. A longitudinal study (2018-2022) of 54 preschoolers with ASD from different kindergartens in Kazan is presented. The dynamics of the development of skills of children with ASD in longitudinal study is minimal, contradictory, depends not on age, but on the complexity of the defect.